Long-Lasting Myocardial and Skeletal Muscle Damage Evidenced by Serial CMR During the First Year in COVID-19 Patients From the First Wave - Filippetti, Laura; Pace, Nathalie; Louis, Jean-Sebastien; Mandry, Damien; Goehringer, François; Rocher, Maria-Soledad; Jay, Nicolas; Selton-Suty, Christine; Hossu, Gabriela; Huttin, Olivier; Marie, Pierre-Yves (Frontiers in Cardiovascular Medicine, 2022)
Introduction This observational CMR study aims to characterize left-ventricular (LV) damage, which may be specifically attributed to COVID-19 and is distant in time from the acute phase, through serial CMR performed during the first year in patients with no prior cardiac disease. Methods This study included consecutive patients without any prior history of cardiac disease but with a peak troponin-Ic > 50 ng/ml at the time of the first COVID-wave. All had a CMR in the first months after the acute phase, and some had an additional CMR at the end of the first year to monitor LV function, remodeling, and abnormalities evocative of myositis and myocarditis - i.e., increased T1/T2 relaxation times, increased extracellular volume (ECV), and delayed contrast enhancement. Results Nineteen consecutively admitted COVID-19 patients (17 men, median age 66 [57–71] years) were included. Eight (42%) had hypertension, six (32%) were obese, and 16 (84%) had suffered an acute respiratory distress syndrome. The 1st CMR, recorded at a median 3.2 [interquartile range: 2.6–3.9] months from the troponin peak, showed (1) LV concentric remodeling in 12 patients (63%), (2) myocardial tissue abnormalities in 11 (58%), including 9 increased myocardial ECVs, and (3) 14 (74%) increased ECVs from shoulder skeletal muscles. The 2nd CMR, obtained at 11.1 [11.0–11.7] months from the troponin peak in 13 patients, showed unchanged LV function and remodeling but a return to normal or below the normal range for all ECVs of the myocardium and skeletal muscles. Conclusion Many patients with no history of cardiac disease but for whom an increase in blood troponin-Ic ascertained COVID-19 induced myocardial damage exhibited signs of persistent extracellular edema at a median 3-months from the troponin peak, affecting the myocardium and skeletal muscles, which resolved within a one-year time frame. Associations with long-COVID symptoms need to be investigated on a larger scale now. Clinical Trial Registration NCT04753762 on the ClinicalTrials.gov site.